Analysis of the descriptive and psychometric characteristics of the internal structure of the ribs in Spanish - López-Fernández, Verónica; Merino-Soto, César; Maldonado Fruto, María Luisa; Orozco Garavito, César Augusto (Creativity Research Journal, 2019)
This study analyzed the internal structure of the Runco Ideational Behavior Scale (RIBS) in a sample of 116 Spanish-speaking individuals. The characteristics of the items and the structural relationship with the construct were analyzed. The results supported a 2-factor model and showed good discrimination. The reliability of the scores was satisfactory for group and individual descriptive purposes. The application of hierarchical modeling seemed to justify a second order dimension, but showed little variance. The results obtained are discussed and an interpretation of the findings is proposed. The RIBS can be an adequate and relevant instrument in Spanish sample to measure creativity.
Keywords: JCR; Scopus